Diabetes-related instrument to assess preventive behaviors among adolescents (DIAPBA): a tool development and psychometric research - Ameneh Pooresmaeil Dorosteh; Mohtasham Ghaffari; Sakineh Rakhshanderou; Yadollah Mehrabi (BMC, 2024)
Abstract Background Type 2 diabetes is a chronic but preventable disease that is on the rise among adolescents. Evaluating adolescents' behavior and planning to prevent it require a valid and reliable instrument. This study aims at designing a psychometric instrument to measure adolescents' behavior with respect to type-2 diabetes. Research Design and methods In this methodological research, 770 students (adolescent boys and girls aged 13-15 years) participated through multistage sampling. The Inclusion criteria were: junior high school students, students' willingness for participation and not suffering from type-1 or type-2 diabetes. The questionnaire was designed by examining the relevant literature and the existing questionnaires as well as considering the research team's comments. The validity of the study was determined through face validity and content validity both quantitatively and qualitatively. The construct validity was determined through exploratory and confirmatory factor analysis. Reliability was measured via intraclass consistency coefficient (ICC) and internal consistency reliability was measured by Cronbach Alpha. SPSS 16 and Eq. 6.1 were used for data analysis. Results At first, a list of 47 initial items was designed and compiled, and after by removing similar (10 questions) or inappropriate sentences (12 questions), a draft questionnaire with 25 questions was designed. No items were removed in the face validity phase. Based on exploratory factor analysis, the number of items in the questionnaire was reduced to 20 items and was categorized in five dimensions of stress management, healthy food/healthy diet, unhealthy food/unhealthy diet, high-risk behavior, and self-care. The results of confirmatory factor analysis confirmed the model. The internal consistency coefficient was confirmed measuring Cronbach Alpha at 0.70 with ICC = 0.80. Conclusion The questionnaire designed has standard psychometric properties to assess adolescents' behavior with respect to type-2 diabetes prevention. The reliability and the validity of the questionnaire as well as its general structure were confirmed.